Chopped carbon fiber reinforced carbon-ceramic composite material and preparation method thereof
By using chopped carbon fiber and other raw materials, the preparation process of carbon ceramic composite materials is simplified, the problem of slow density of carbon matrix in the prior art is solved, and the high strength, wear resistance and efficient production of the material is achieved.
Patent Information
- Application Number
- CN202311573462.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-23
- Publication Date
- 2024-12-13
AI Technical Summary
In the existing preparation methods of carbon fiber reinforced carbon ceramic composite materials, the carbon matrix density enhancement process progresses slowly and the process requirements are high, which limits the application of materials.
The carbon ceramic composite materials are prepared by pre-pressing, hot pressing, carbonization and silicon permeation, using chopped carbon fiber, silicon carbide powder, carbon powder, boron-containing phenolic resin, graphene and Fe-MOFs, and the density is simplified. process.
It improves the strength, wear resistance and thermal conductivity of the material, reduces material costs, shortens density increase time, improves production efficiency, and improves mechanical properties and mechanical processing.
Abstract
Description
Technical Field
[0001] The invention relates to the field of carbon-ceramic composite materials, in particular to a chopped carbon fiber reinforced carbon-ceramic composite material and a preparation method thereof. Background Art
[0002] Carbon fiber reinforced carbon ceramic composites were born in the 1980s. They have high densification, excellent environmental adaptability, long service life, and excellent performance. They are excellent thermal structural materials. At the beginning of this century, they were applied to the friction field and became the latest generation of high-performance brake materials. They are new multifunctional ceramic-based composite materials with huge development space and potential.
[0003] So far, there are many relatively mature preparation methods for carbon fiber reinforced carbon ceramic composites. The more commonly used methods are chemical vapor infiltration (CVI) and polymer impregnation pyrolysis (PIP). Both preparation methods require long carbon fibers to be woven into a carbon fiber blank, and then the carbon matrix of the blank is densified by CVI or PIP, and finally the carbon matrix is reacted into a silicon carbide matrix by siliconization to finally complete the carbon fiber reinforced carbon ceramic composite. The carbon matrix densification process of these two methods progresses slowly, takes a lot of time, and may need to be repeated, and has high process requirements, which greatly limits the application of carbon fiber reinforced carbon ceramic composites. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a chopped carbon fiber reinforced carbon-ceramic composite material and a preparation method thereof.
[0005] The technical solutions adopted are as follows: A chopped carbon fiber reinforced carbon-ceramic composite material is prepared from the following raw materials in parts by weight: 10-60 parts of chopped carbon fibers, 10-60 parts of silicon carbide powder, 10-60 parts of carbon powder, 10-60 parts of boron-containing phenolic resin, 0.1-10 parts of graphene, and 1-5 parts of Fe-MOFs.
[0006] The present invention also provides a method for preparing a chopped carbon fiber reinforced carbon-ceramic composite material: Chopped carbon fibers, silicon carbide powder, carbon powder, boron-containing phenolic resin, graphene and Fe-MOFs are uniformly mixed to obtain a mixture, the mixture is pre-pressed, hot-pressed and carbonized to obtain a green body, and the green body is siliconized to obtain the carbon-ceramic composite material.
[0007] Furthermore, the pre-pressing temperature is 20-30° C. and the pressure is 3-6 MPa.
[0008] Furthermore, the pressure of the hot pressing molding is 20-50MPa, and the temperature is increased in a stepwise manner, first from room temperature to 120-140°C, kept warm for 10-40min, and then increased to 180-200°C, kept warm for 10-40min.
[0009] Furthermore, during the hot pressing process, the pressure can be released several times in a timely manner according to the pressing conditions of the mold.
[0010] Furthermore, during carbonization, the vacuum degree of the furnace is ≤100Pa, the carbonization temperature is 800-1200°C, the carbonization time is 1-3h, the heating rate during carbonization is 0.5-2°C / min, and the carbonization is naturally cooled to room temperature after completion.
[0011] Furthermore, the siliconizing operation is specifically as follows: The silicon powder is evenly spread in a graphite crucible, the amount of silicon powder is 1.5-2.5 times the weight of the blank, the blank is supported by a graphite gasket so that it is suspended above the silicon powder, and the gap between the blank and the silicon powder is 1-5mm, the graphite crucible is placed in a high-temperature vacuum furnace, the high-temperature vacuum furnace is evacuated to below 100Pa, and then argon gas is introduced for protection, the temperature is increased to 1500-2000℃ at a rate of 0.5-2℃ / min, and the temperature is kept for 1-4h, and then naturally cooled to room temperature.
[0012] Furthermore, the density of the green body after siliconization is ≥2.4g / cm 3 .
[0013] Furthermore, the preparation method of the Fe-MOFs is as follows: Add soluble iron salt and trimesic acid into water, stir evenly and put into a constant temperature water bath, react at 90-95°C for 18-36h, filter out the obtained product, wash and dry.
[0014] Furthermore, the preparation method of the boron-containing phenolic resin is as follows: Mix formaldehyde, phenol and ammonia water, stir and heat to 60-70℃ for reaction for 2-4h, then cool to below 50℃, add boric acid, heat to 90-120℃ and keep warm for reaction for 1-2h, finally remove small molecules by vacuum distillation.
[0015] Beneficial effects of the present invention: The present invention provides a chopped carbon fiber reinforced carbon-ceramic composite material. The chopped carbon fiber serves as the skeleton of the carbon-ceramic composite material, which can improve the strength, wear resistance, thermal conductivity, etc. of the carbon-ceramic composite material, and can also effectively prevent the expansion of cracks, thereby solving the brittleness problem of the carbon-ceramic composite material to a certain extent. The addition of silicon carbide powder can also prevent crack propagation, reduce the amount of chopped carbon fiber, and reduce material costs. At the same time, during the siliconization process, silicon carbide powder can form a better interface with the material matrix by diffusion, reduce internal stress, and improve mechanical properties. Carbon powder can provide carbon to participate in the reaction for the system, reduce the amount of boron-containing phenolic resin used, and prevent resin overflow during hot pressing due to excessive resin. The high thermal conductivity of carbon powder can also improve the heat conduction during hot pressing, which is helpful for hot pressing. Boron-containing phenolic resin acts as an adhesive in the hot pressing stage, bonding the components into a whole to ensure the formability of the material, and provides carbon for the reaction for the system after carbonization. Boron-containing phenolic resin introduces boron element into the phenolic main chain structure, which can increase the residual carbon rate of the resin and the density of the carbon-ceramic composite material. Boron carbide will be generated during the carbonization process, which plays a role in toughening and improving the mechanical properties. Graphene can improve the mechanical properties of the material after hot pressing and improve the machinability.
[0016] The addition of Fe-MOFs can reduce the graphitization temperature of boron-containing phenolic resin. The Fe and Fe3C particles generated by the pyrolysis of Fe-MOFs serve as active sites for the rearrangement of non-graphite carbon, improve the graphitization efficiency, and promote the formation of graphitized carbon nanotubes. Graphitized carbon nanotubes can "reinforce" carbon-ceramic composites at the nanoscale and inhibit the expansion of organizational defects and destructive cracks inside the material. The carbon-ceramic composite material prepared by the present invention has good mechanical properties and excellent wear resistance, and the material densification process is relatively rapid and does not need to be repeated, thus saving time and improving production efficiency. DETAILED DESCRIPTION
[0017] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0018] Chopped carbon fiber: 5-20 mm in length, purchased from Toray New Materials (Guangdong) Co., Ltd. Silicon carbide powder: α type, 200-400 mesh, purchased from Zhengzhou Kerui Refractory Materials Co., Ltd.; Carbon powder: 200-400 mesh, purchased from Beijing October New Materials Technology Co., Ltd.; Boron-containing phenolic resin: Homemade, the preparation method is as follows: Add 94g of molten phenol and 0.94g of ammonia water into a 500ml four-necked flask with a condenser and a thermometer, start the stirrer and stir for 30min, then slowly add 105.5g of formaldehyde into the reaction system within 1.5h, then heat to 70℃ and stir for 3h, cool to 50℃, add 18.6g of boric acid, then heat the reaction solution to 120℃ within 1h and keep it warm for 2h, cool to 75℃, and then remove small molecules by reduced pressure distillation at -0.01MPa.
[0019] Graphene: 200-400 mesh, purchased from Shandong Xiangzhao New Materials Co., Ltd.
[0020] Fe-MOFs: Homemade, preparation method is as follows: Add 54 g of ferric nitrate nonahydrate and 37.8 g of trimesic acid into 250 mL of deionized water, mix and stir evenly, put into a constant temperature water bath, and let it react at 95°C for 24 hours. Filter out the product, wash it with a mixed solution of ethanol and water (volume ratio of 1:1), and then put it into a vacuum drying oven and dry it at 120°C for 10 hours. Example 1
[0021] A method for preparing a chopped carbon fiber reinforced carbon ceramic composite material: Weigh the raw materials: 50 parts of chopped carbon fiber, 30 parts of silicon carbide powder, 30 parts of carbon powder, 50 parts of boron-containing phenolic resin, 5 parts of graphene, and 3 parts of Fe-MOFs, add the chopped carbon fiber, silicon carbide powder, carbon powder, boron-containing phenolic resin, graphene and Fe-MOFs into a drum ball mill, mix them at a speed of 100 r / min for 120 min to obtain a mixture, pre-press the mixture at 5 MPa for 30 s at room temperature, then pressurize it to 40 MPa, heat it to 140 ° C while maintaining the pressure, heat it for 40 min, then heat it to 200 ° C, heat it for 30 min to obtain a rough blank, send the rough blank into a carbonization furnace for carbonization, and carbonize it. The vacuum degree of the furnace is 80±10Pa, the carbonization temperature is 1200℃, the carbonization time is 2h, the heating rate during carbonization is 1℃ / min, and after the carbonization is completed, it is naturally cooled to room temperature to obtain a green body. The silicon powder is evenly spread in the graphite crucible. The amount of silicon powder is twice the weight of the green body. The green body is supported by a graphite gasket so that it is suspended above the silicon powder. The gap between the green body and the silicon powder is 5mm. The graphite crucible is placed in a high-temperature vacuum furnace, and the high-temperature vacuum furnace is evacuated to 80±10Pa, and then argon is introduced for protection. The temperature is increased to 2000℃ at a rate of 2℃ / min, and kept for 3h, and then naturally cooled to room temperature. Example 2
[0022] A method for preparing a chopped carbon fiber reinforced carbon ceramic composite material: Weigh the raw materials: 60 parts of chopped carbon fiber, 60 parts of silicon carbide powder, 60 parts of carbon powder, 60 parts of boron-containing phenolic resin, 10 parts of graphene, and 5 parts of Fe-MOFs. Add the chopped carbon fiber, silicon carbide powder, carbon powder, boron-containing phenolic resin, graphene and Fe-MOFs into a drum ball mill, mix them at a speed of 100 r / min for 120 min to obtain a mixture, pre-press the mixture at room temperature at 6 MPa for 30 s, then pressurize it to 50 MPa, maintain the pressure and heat it to 140°C, keep it warm for 40 min, then heat it to 200°C, keep it warm for 40 min to obtain a rough blank, send the rough blank into a carbonization furnace for carbonization, and carbonize it at room temperature. The vacuum degree of the furnace is 80±10Pa, the carbonization temperature is 1200℃, the carbonization time is 3h, the heating rate during carbonization is 2℃ / min, and after the carbonization is completed, it is naturally cooled to room temperature to obtain a green body. The silicon powder is evenly spread in the graphite crucible, and the amount of silicon powder is 2.5 times the weight of the green body. The green body is supported by a graphite gasket so that it is suspended above the silicon powder. The gap between the green body and the silicon powder is 5mm. The graphite crucible is placed in a high-temperature vacuum furnace, and the high-temperature vacuum furnace is evacuated to 80±10Pa, and then argon is introduced for protection. The temperature is increased to 2000℃ at a rate of 2℃ / min, and it is kept warm for 4h and then naturally cooled to room temperature.
[0023] Comparative Example 1: It is basically the same as Example 1, except that commercially available 2123 phenolic resin is used instead of the boron-containing phenolic resin.
[0024] Comparative Example 2: It is basically the same as Example 1, except that commercially available 2402 phenolic resin is used instead of the boron-containing phenolic resin.
[0025] Comparative Example 3: basically the same as Example 1, except that no graphene is added.
[0026] Comparative Example 4: basically the same as Example 1, except that no Fe-MOFs are added.
[0027] Performance test: The carbon-ceramic composite materials prepared in Examples 1-2 and Comparative Examples 1-4 of the present invention were made into samples for performance testing. The specific test methods are as follows: The density of the sample was tested by Archimedes drainage method; The flexural strength and fracture toughness of the composite materials were tested on an electronic universal testing machine with a loading speed of 0.5 mm / min, a sample size of 30 mm×5 mm×4 mm, and a fixed span of 20 mm. The wear resistance was tested on a friction and wear tester, model: MM-200; sample size: 7mm×7mm×30mm; friction type: sliding dry friction; the material of the grinding pair is 9Cr18, the size is φ50mm×10mm, the surface roughness is 1.6, the test conditions are: speed 200r / min, pressure 250N, running time 10h; Table 1 below summarizes the performance test results of the carbon-ceramic composite materials prepared in various embodiments and comparative examples; Table 1: ; It can be seen from Table 1 above that the carbon-ceramic composite material prepared in the present invention has good mechanical properties and excellent wear resistance.
[0028] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A chopped carbon fiber reinforced carbon ceramic composite material, characterized in that: It is prepared from the following raw materials in parts by weight: 10-60 parts of chopped carbon fibers, 10-60 parts of silicon carbide powder, 10-60 parts of carbon powder, 10-60 parts of boron-containing phenolic resin, 0.1-10 parts of graphene, and 1-5 parts of Fe-MOFs; The preparation method of the Fe-MOFs is as follows: Add soluble iron salt and trimesic acid into water, stir evenly and put into a constant temperature water bath, react at 90-95℃ for 18-36h, filter out the obtained product, wash and dry it; The preparation method of the boron-containing phenolic resin is as follows: Mix formaldehyde, phenol and ammonia water, stir and heat to 60-70℃ for reaction for 2-4h, then cool to below 50℃, add boric acid, heat to 90-120℃ and keep warm for reaction for 1-2h, finally remove small molecules by vacuum distillation.
2. A method for preparing the chopped carbon fiber reinforced carbon ceramic composite material according to claim 1, characterized in that: Chopped carbon fibers, silicon carbide powder, carbon powder, boron-containing phenolic resin, graphene and Fe-MOFs are uniformly mixed to obtain a mixture, the mixture is pre-pressed, hot-pressed and carbonized to obtain a green body, and the green body is siliconized to obtain the carbon-ceramic composite material.
3. The method for preparing the chopped carbon fiber reinforced carbon ceramic composite material according to claim 2, characterized in that: The pre-pressing temperature is 20-30° C. and the pressure is 3-6 MPa.
4. The method for preparing the chopped carbon fiber reinforced carbon ceramic composite material according to claim 2, characterized in that: The pressure of the hot pressing molding is 20-50MPa, and the temperature is increased in a stepwise manner, first from room temperature to 120-140°C, kept warm for 10-40min, then increased to 180-200°C, and kept warm for 10-40min.
5. The method for preparing the chopped carbon fiber reinforced carbon ceramic composite material according to claim 4, characterized in that: During hot pressing, the pressure is released several times according to the pressing conditions of the mold.
6. The method for preparing the chopped carbon fiber reinforced carbon ceramic composite material according to claim 2, characterized in that: During carbonization, the vacuum degree of the furnace is ≤100Pa, the carbonization temperature is 800-1200°C, the carbonization time is 1-3h, the heating rate during carbonization is 0.5-2°C / min, and it is naturally cooled to room temperature after carbonization is completed.
7. The method for preparing the chopped carbon fiber reinforced carbon ceramic composite material according to claim 2, characterized in that: The operation of siliconizing is as follows: The silicon powder is evenly spread in a graphite crucible, the amount of silicon powder is 1.5-2.5 times the weight of the blank, the blank is supported by a graphite gasket so that it is suspended above the silicon powder, and the gap between the blank and the silicon powder is 1-5mm, the graphite crucible is placed in a high-temperature vacuum furnace, the high-temperature vacuum furnace is evacuated to below 100Pa, and then argon gas is introduced for protection, the temperature is increased to 1500-2000℃ at a rate of 0.5-2℃ / min, and the temperature is kept for 1-4h, and then naturally cooled to room temperature.
8. The method for preparing the chopped carbon fiber reinforced carbon ceramic composite material according to claim 7, characterized in that: The density of the green body after siliconization is ≥2.4g / cm 3 .
Citation Information
Patent Citations
Carbon-ceramic composite brake disc and preparation method thereof
CN103553695A
Preparation method for graphene modified carbon / carbon pantograph contact strip used for electric locomotive
CN108585913A
Magnesia carbon brick using phenolic resin added with catalyst
CN112028613A
Carbon-metal organic framework composite, manufacturing method thereof, and lithium air battery including the same
US20220158157A1
Cited By
Carbon fiber composite material as well as preparation method and application thereof
CN120794695A
Carbon-ceramic composite material and preparation method of carbon-ceramic composite material by utilizing cured resin waste
CN122301571A
